Urgensi Quantum Ikhlas untuk Kesehatan Mental di Masa Pandemi Covid-19 - N. Nurhalimah; Agus Aditoni (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2021)
This article aims to find out the urgency of quantum ikhlas to achieve mental health amid the uncertainty of the end of Covid-19. Quantum ikhlas is the integration between ikhlas and knowledge. Quantum is something that is not invisible, but the more subtle it is, the greater its power. During the Covid-19 pandemic, health challenges are the main target, both physically and mentally. Likewise with mental health, where during the pandemic the cases are getting bigger. In this position, religion has provided a solution. One of them is by teaching ikhlas in accepting all the provisions that Allah has given. Even though in reality today's society often grumbles and blames the situation. No wonder this attitude makes him even more disappointed, frustrated, stressed and depressed. This study uses descriptive qualitative research, type of literature. By collecting all sources, both page articles, journals, and books. Only then analyzed. The results of this study, quantum ikhlas has an urgency to achieve mental health in the face of a pandemic. Because with ikhlas, someone will accept the situation and bring peace within him.